PENGARUH KECERDASAN BUATAN DAN KEPUASAN PELANGGAN DALAM REKOMENDASI PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI E-COMMERCE - Rizma Adelia; Hani Hasanah; Laras Annisa Ulfitri Nedi (LPPM Politeknik Pratama, 2025)
This study aims to analyze the influence of Artificial Intelligence (AI) and customer satisfaction in product recommendation systems on consumer purchasing decisions in e-commerce platforms.. This research employs a quantitative approach with purposive sampling, involving 160 respondents who have experienced AI-based product recommendations in e-commerce. Data were collected through online questionnaires and analyzed using smartpls 3. The results reveal that artificial intelligence significantly influences purchasing decisions on a partial basis. Likewise, customer satisfaction also shows a positive and significant effect. Simultaneously, both artificial intelligence and customer satisfaction have a significant impact on consumer purchasing decisions. These findings provide valuable implications for e-commerce platforms to develop more accurate, relevant, and user-centered recommendation systems.